A safety review of drug treatments for patients with systemic immunoglobulin light chain (AL) amyloidosis. Issue 4 (3rd April 2021) - Nuvolone, Mario; Basset, Marco; Palladini, Giovanni
ABSTRACT: Introduction: In AL amyloidosis, a usually small plasma cell clone secretes unstable, amyloid-forming light chains, causing cytotoxicity and progressive (multi)organ function deterioration. Treatment aims at reducing/eradicating the underlying clone, to reduce/zero the supply of the amyloidogenic protein and halt the amyloidogenic cascade. Areas covered: Safety data of alkylating agents, proteasome inhibitors, immunomodulatory drugs, and monoclonal antibodies from clinical trials are reviewed. Expert opinion: Drugs used to treat AL amyloidosis are derived from experience with multiple myeloma or other B cell malignancies. However, treating AL amyloidosis is particularly challenging, as it implies delivering anti-neoplastic therapy to a hematologic malignancy directly causing (multi)organ function deterioration, often in elderly subjects with other comorbidities and polypharmacotherapy. This unique combination translates in increased patients' frailty and higher sensitivity toward treatment-related toxicities. Therefore, dose/schedule adjustments and special precautions are needed when translating treatment experience from multiple myeloma or other B cell malignancies to AL amyloidosis. Treatment of patients with AL amyloidosis should be risk adapted, tailored to individual patients' risk profile, considering the type and extent of organ involvement, and eventual comorbidity. As several classes of effective anti-plasma cell or B cell drugs are available, therapeutic choices are also influenced by individual drug's safety profile.